Life history inhomogeneity in Baltic Sea whitefish populations revealed by otolith strontium signatures – identification of stocked fish - Henry Hägerstrand; Yvette Heimbrand; Erkki Jokikokko; Joakim Slotte; Jan-Olof Lill (Frontiers in Marine Science, 2015)
European whitefish (Coregonus lavaretus) occurs as two ecotypes in the Gulf of Bothnia, Baltic Sea (Fig. 1). The ecotypes, anadromous river spawning and stationary sea spawning whitefish, mix at sea off breeding location and time. They have similar outer features. However, the former group has higher number (29.9±2.14) of gill rakers than the latter one (26.7±2.21), as shown by studies from the Finnish west coast (Himberg et al. 2015). To preserve naturally reproducing whitefish populations and support fisheries, massive stocking of mainly river spawning whitefish into rivers, river estuaries and sea is undertaken. The stocked fish is mainly hatched and raised in freshwater ponds over the summer before being released in the autumn. The ratio of wild-born/stocked adult whitefish caught during migration as well as at feeding grounds remains unknown. Methods to clarify the issue are not well developed. Mass-marking of young fish is a possibility (spray-marking, alizarin), but large scale sampling is needed to give reliable results. In the present study we applied strontium analysis of the otolith core in polished otoliths to shed light on this issue. Materials and methods. The Gulf of Bothnia with its brackish water stretches ~725 km from the Aland Islands in the south, to the Tornio region in the north (Fig. 1). Whitefish was caught in 2013 during ascending to spawn in northern River Tornionjoki and in mixed sea fisheries at southern feeding grounds (Åland Islands, Kobba Klintar). Otoliths were removed from ten fishes from the river (“river spawners”, average gill raker number 30.1±1.2), and from ten fishes caught at sea; five with 27 gill rakers (“sea spawners”) and five with 30 gill rakers (“river spawners”). The otoliths (sagittae) were polished and the strontium concentrations in the core were determined with PIXE (Lill et al. 2015). Results and discussion. The results from the analyses of strontium in the core of the otoliths are intricate (Table 1, Supplemental Data). One of the five fishes with 27 gill rakers caught at sea had spent time as juvenile in fresh water which was revealed by the low strontium concentration (815 µg/g) in the otolith core. This fish was probably a sea spawner from the local hatchery (Guttorp, Åland Islands), where only sea spawners are raised. Interestingly, three fishes out of the five with 30 gill rakers caught at sea showed a fresh water signature in the natal region of the otolith (core strontium ≤1383 µg/g). This result is in line with annual stocking of vast amount of particularly the river spawning type of whitefish in rivers and at sea along the Finnish west coast and in the Archipelago Sea. The strontium concentrations in the otolith cores of whitefish from River Tornionjoki were higher than that of the four otoliths with low core strontium from fishes caught at sea (Table 1). Supposing that this latter group represent stocked fish raised in freshwater ponds, the vast majority of River Tornionjoki whitefish is naturally reproduced fish. This is plausible because in River Tornionjoki, the major whitefish spawning river in Finland, no larger stocking have been made since 1990s (Jokikokko and Huhmarniemi 2014). In conclusion, the concentration of otolith core strontium differs in whitefish hatched in fresh-water and in whitefish hatched in river water or in brackish Baltic Sea water. This difference can be used to reveal stocked whitefish. Barium concentration may be an even better indicator in this respect than strontium, as previous results indicate (Hägerstrand et al., 2015). Stocked river spawning whitefish appear in large amount at the southern feeding grounds around the Åland Islands, as already indicated by e.g. Leskelä et al. (2009).